Local recurrence of pheochromocytoma in multiple endocrine neoplasia type 2A: a diagnostic and therapeutic challenge. Issue 3 (12th February 2016) - Tramunt, Blandine; Buffet, Alexandre; Grunenwald, Solange; Vezzosi, Delphine; Bennet, Antoine; Huyghe, Eric; Zerdoud, Slimane; Caron, Philippe
Key Clinical Message: In a patient with multiple endocrine neoplasia type 2A (MEN2A), an inverted physiological ratio between urinary normetanephrines and metanephrines is an early marker of recurrence in epinephrine‐secreting pheochromocytoma, and 131I MIBG treatment appears to be a useful therapeutic option in order to avoid multiple invasive surgical procedures in pheochromocytomatosis. Abstract : In a patient with multiple endocrine neoplasia type 2A (MEN2A), an inverted physiological ratio between urinary normetanephrines and metanephrines is an early marker of recurrence in epinephrine‐secreting pheochromocytoma, and 131I MIBG treatment appears to be a useful therapeutic option in order to avoid multiple invasive surgical procedures in pheochromocytomatosis.